Análisis del ahorro fiscal en el procedimiento de subasta inversa y el impacto económico a los proveedores de la entidad SUPERCOM en la ciudad de Quito - Tapia Erazo, Jessica Alexandra (2018)
The following investigation analyzes the fiscal savings that had been generated in the reverse auction procedure and its effects on the suppliers in the contracting entity Superintendence of the Information and Communication, showing how the law of public contracting has influenced positively the process of Reverse auction in 2014, 2015 and 2016 generating significant fiscal savings for the state. The methodology applied was an explanatory and descriptive type, where relevant information of the public procurement procedures carried out the evidence in the SUPERCOM, as well as the analysis of data faced by investigative techniques corroborating that the participating companies are mostly medium and large companies, and that there were different factors that were relevant for the economy of these suppliers of the 5 contracting entity. The Superintendence of Information and Communication does not generate sustainable economic growth causing some of them to decline the participation in the public procurement process that promotes the Ecuadorian state that meets the objective for which the LOSNCP was created. All these arguments analyzed from qualitative and quantitative perspectives to those involved in this activity.